Web-Based Teacher Performance Assessment Information System Using Simple Additive Weighting Method - Saepul Aripiyanto; Abdul Muhyiddin; Baenil Huda (Information System; Universitas Buana Perjuangan Karawang, 2021)
SMP IT Nurul Huda Batujaya is one of the educational institutions for school students in Batujaya District, Karawang Regency. The research objective is to develop teacher performance appraisal. The research method using qualitative methods aims to describe the data analysis in a narrative manner. Methods of data collection by observation, interviews, and literature study. Teacher performance assessment is still done manually by using Microsoft Excel and Microsoft Word. Other problems are needed, namely, the high cost of printing documents from each teacher, the documents submitted to the administration department are often damaged and confused, the assessment team must carry a lot of documents during the assessment, and errors during the assessment recapitulation. This can have an impact on delays in the teacher performance assessment process. The system development method uses the waterfall, Hypertext Preprocessor (PHP) programming language, MySQL, and the Simple Additive Weighting (SAW) method. The results achieved in this study can create and design a teacher performance appraisal information system to help the assessment process quickly and correctly to reduce the occurrence of errors.